ANALISIS PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KEPUASAN PELANGGAN (Studi Kasus di Hotel Grand Mutiara Pangkalpinang) - Novalia; Astuti, Nelly; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2018)
The purpose of this study is to know how the implementation of Total Quality Management as measured by Obsession towards quality, Teamwork, Education and training, Engagement and empowerment. This research method uses regression analysis with simultaneous and partial test, testing using help program spss version 22, with a total sample of 100 people. Research results show that : The Obsession towards quality has a significant relationship to customer satisfaction of 5,251. Teamwork has a significant relationship to customer satisfaction of 5,161. Education and training have a significant relationship to customer satisfaction of 5,437. Employees engagement and empowerment have a significant relationship to customer satisfaction of 0,431. Obsession towards quality, Teamwork, Education and training, Employees engagement and empowerment together towards customer satisfaction equal to 7,873. Based on the results of the study, the researcher concludes that customer satisfaction in Grand Mutiara Hotel Pangkalpinang can be improved through Total Quality Management.